2014
DOI: 10.1002/hep.27389
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of clinical outcomes in Asian patients with chronic hepatitis B using enhanced liver fibrosis test

Abstract: Serum fibrosis markers, such as the enhanced liver fibrosis (ELF) test, have been suggested as alternatives for liver biopsy (LB) in assessing liver fibrosis. We investigated the efficacy of the ELF test in predicting development of liver-related events (LREs) in patients with chronic hepatitis B (CHB). A total of 170 patients (103 men; 60.6%) with CHB who underwent LB and serological tests for determining ELFs were enrolled. All patients were followed up to monitor LRE development, defined as hepatic decompen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…A few other studies conducted in the pretransplant setting have also shown that noninvasive fibrosis tools are accurate in predicting prognosis of patients with chronic liver diseases. 6,7,15,29 In this era of developing noninvasive and safer approaches to diagnosis and screening, our findings have significant implications in the ongoing care of patients following LT. First, the transplant hepatologist, or any other physician involved in the care of these patients, may employ fibrosis biomarkers to screen LT recipients for prognostic evaluation, without having to resort to the invasive and costly procedure of liver biopsy. These tests could be easily repeated to monitor LT recipients and predict patient and graft outcome because our study reveals that the evolution of fibrosis scores over time is also predictive of prognosis.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A few other studies conducted in the pretransplant setting have also shown that noninvasive fibrosis tools are accurate in predicting prognosis of patients with chronic liver diseases. 6,7,15,29 In this era of developing noninvasive and safer approaches to diagnosis and screening, our findings have significant implications in the ongoing care of patients following LT. First, the transplant hepatologist, or any other physician involved in the care of these patients, may employ fibrosis biomarkers to screen LT recipients for prognostic evaluation, without having to resort to the invasive and costly procedure of liver biopsy. These tests could be easily repeated to monitor LT recipients and predict patient and graft outcome because our study reveals that the evolution of fibrosis scores over time is also predictive of prognosis.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, these noninvasive tools have meaningful prognostic utility in identifying patients at high risk for liver-related complications, death, and need for LT in chronic viral hepatitis and NAFLD. 6,7,15 A number of them have also been specifically validated in LT recipients, and the reported accuracy is similar to the pre-LT setting. [16][17][18][19][20][21][22] One report thus far has suggested the prognostic value of a noninvasive fibrosis tool in the posttransplant setting.…”
mentioning
confidence: 99%
“…We did not employ MELD score to predict clinical outcomes in this study. Indeed, previous prognostic studies showed that MELD score is not useful to predict clinical outcomes when the study population does not include mostly cirrhotic patients [26]. Diabetes is a known risk factor for malignancy and fibrosis progression rate in chronic liver diseases of various etiologies [39].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive methods can also diagnose and grade steatosis, including radiologic techniques, such as ultrasonography [21] and Xenon-133 liver scan [22], and biomarkers such as hepatic steatosis index (HSI) [23]. Non-invasive tools for liver fibrosis may help identify patients at high risk for liver-related complications or death in chronic hepatitis C and B, and in NAFLD [2426]. No study has specifically investigated the prognostic performance of non-invasive methods for liver fibrosis and hepatic steatosis for prediction of clinical outcomes in NASH as compared to the gold standard methods to diagnose liver fibrosis (histology) and clinically significant portal hypertension (HVPG).…”
Section: Introductionmentioning
confidence: 99%
“…FibroTest, enhanced liver fibrosis panel) [92,93]. Abnormal fibrosis biomarkers are associated with HCC development [94]. Further studies are required to evaluate the possibility of combining these serum tests with other clinical parameters to improve HCC prediction.…”
Section: Diagnosis Of Cirrhosis As the Achilles Heelmentioning
confidence: 98%